KNOWLEDGE MODELING FOR A RELATIONAL DATABASE IN ONTOLOGY WEB LANGUAGE (OWL) - Huỳnh Tuấn Anh (Tạp chí Khoa học Đại học Đà Lạt)
This paper presents a knowledge modeling method by Ontology Web Language (OWL) for a relational database. The proposed method contains the rules for transforming data in a relational database into Ontology and Axioms for supplementing meaning of a relational database. Based on these rules, data in a relational database could be converted into triples Resource Description Framework (RDF)/OWL for Semantic web applications.